QUALITY OF LIFE OF TRANSEXUAL WOMEN LIVING WITH HIV/AIDS - Paula Daniella de Abreu; Ednaldo Cavalcante de Araújo; Eliane Maria Ribeiro de Vasconcelos; Jefferson Wildes da Silva Moura; Isabela de Lucena Heráclio; Zailde Carvalho dos Santos; Claudia Benedita dos Santos (Universidade Federal do Paraná, 2019)
Objective: To understand the quality of life of transsexual women living with HIV/AIDS. Methods: This was a qualitative, descriptive, exploratory study, carried out in 2017 with six transsexual women at a reference hospital for HIV/AIDS in Pernambuco, Brazil. The interviews were recorded and transcribed using the Interface de R pour les Analyses Multidimensionnelles de Textes et de Questionnaires, using the similitude analysis technique.Results: The following classes emerged: "Vulnerability to HIV/AIDS and implications for coping"; and "HIV/AIDS treatment adherence and the programming context".Final considerations: The condition of living with HIV/AIDS for transsexual women goes beyond the disease, involving intimate suffering in terms of social violence, denied human rights, and vulnerability, which limits their personal and social development and impacts the totality of human conditions to reach a high quality of life.